2021
DOI: 10.1101/2021.02.23.432559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Stress Alters Astrocyte Morphology in Mouse Prefrontal Cortex

Abstract: Background: Neuromorphological changes are consistently reported in the prefrontal cortex (PFC) of patients with stress-related disorders and in rodent stress models, but the effects of stress on astrocyte morphology and potential link to behavioral deficits are relatively unknown. Methods: To answer these questions, transgenic mice expressing green fluorescent protein (GFP) under the glial fibrillary acid protein (GFAP) promotor were subjected to 7, 21 or 35 days of chronic restraint stress (CRS). CRS behavi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 94 publications
2
10
0
2
Order By: Relevance
“…Other tests measuring anxiety and anhedonia exist however most cannot be repeated hindering longitudinal analysis (Nollet et al, 2013; Planchez et al, 2019). Secondly, in our attempt to avoid ceiling effects of CRS and detect susceptibility, we used a less severe protocol for a shorter duration than our previous studies (Codeluppi et al, 2021; Misquitta et al, 2021; Prevot et al, 2019). It is possible that a longer CRS protocol is needed to observe greater susceptibility associated with cHOA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other tests measuring anxiety and anhedonia exist however most cannot be repeated hindering longitudinal analysis (Nollet et al, 2013; Planchez et al, 2019). Secondly, in our attempt to avoid ceiling effects of CRS and detect susceptibility, we used a less severe protocol for a shorter duration than our previous studies (Codeluppi et al, 2021; Misquitta et al, 2021; Prevot et al, 2019). It is possible that a longer CRS protocol is needed to observe greater susceptibility associated with cHOA.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we identified that CRS-exposed and control animals spend equivalent amounts of time avoiding the food zone in favor of the shelter during the spotlight challenge. However, CRS animals subjected to chronic stress continue to avoid the food zone after the challenge (Codeluppi et al, 2021; Misquitta et al, 2021; Prevot et al, 2019). This is a behavior, is highly specific of chronic stress exposure, defined as “residual avoidance” (RA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic stress-induced elevated or sustained Glu levels causes excitotoxic effects via enhanced extrasynaptic signaling activity (Hardingham and Bading, 2010;Popoli et al, 2011;Pál, 2018). These alterations were linked to maladaptive changes to the structure and function of neurons (Musazzi et al, 2015;Lener et al, 2017) and glial cells (Banasr et al, 2010;Sanacora and Banasr, 2013;Mayegowda and Thomas, 2019;Codeluppi et al, 2021). Homeostatic glial cells such as astrocytes play a pivotal role in regulating stress-induced glutamatergic dysfunction (Popoli et al, 2011;Rajkowska and Stockmeier, 2013;Sanacora and Banasr, 2013;Abbink et al, 2019) as are accountable for over 80% of Glu reuptake, Glu synthesis and metabolism (Chen et al, 2014;Baek et al, 2019;Fullana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated or sustained Glu levels induced by chronic stress can causes excitotoxic effects via enhanced extrasynaptic signaling activity [48, 51, 52]. These alterations have been linked to maladaptive changes in the structure and function of neurons [53, 54] and glial cells [5558]. Glial cells such as astrocytes play a pivotal role in the homeostatic response to the stress-induced increases in glutamatergic neurotransmission [48, 57, 59, 60] as they are responsible for over 80% of Glu reuptake, Glu synthesis and metabolism [6163].…”
Section: Introductionmentioning
confidence: 99%